Development of Information System for Elderly Care in Terms of Nutrition to Support Quality of Life in Chamai Municipality, Nakhon Si Thammarat - Jinpon, Puangrat; Jueboon, Manita; Limsuwanmanee, Jutaporn; Wichianchuea, Jariyawadee (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
It has been estimated that Thailand will be a “complete aged society” in 2021. Thus, providing the elderly care in the aspect of good nutrition is crucial to reduce the burden on the part of caretakers. This research aims to develop an information system on nutrition of the elderly in Chamai Subdistrict, Nakhon Si Thammarat and distribute the system to state personnel, local community leaders, and interested individuals. Three hundred and twenty two elderly people were selected through probability proportional to size (PPS) sampling, and 52 users of the developed system through purposing sampling. In-depth interviews and questionnaires were used to collect data. The system was developed using SDLC (System Development Life Cycle) process, web technologies and Open Standards software, combining dashboard and Geographic Information System (GIS) techniques. Content analysis was conducted for qualitative data; and percentage, mean and standard deviation, for quantitative ones. Results reveal that the system can store and clearly present nutritional information of the elderly, both in statistical and spatial formats. The developed system was disseminated through forums, documents and social media such as Facebook and Instagram. The system has been used as a tool to support elderly care for Chamai municipality staff and the elderly in the area. This tool can also be useful for people who are interested.